Preliminary cognitive model of a semi-mechanized picking operation (2017)
The current paper develops a pioneering approach to the human factors of picking operations, which are addressed from a cognitive perspective. The model is established through a qualitative methodology, which based on several theories, is articulated and applied to the real situation of a dry foods company. The results combine the cognitive architecture of the operation and its relations with logistic factors to decrease the amount of human error and thus increase the service level. This model provided evidence for three logistic factors, namely, the picking zone type, the order difficulty level and the experience level; furthermore, from the cognitive perspective, attention and memory. © 2017